Impact of changes to procedures on the evaluation of the effectiveness of forms of professional activation in poland - Beata Bieszk-Stolorz; Krzysztof Dmytrów (Economies, 2021)
Active labour market policy is connected with the necessity to account for the funds allocated for it. The conducted analysis forms a part of research on the evaluation of the effects of changes introduced by legal regulations. The aim of this research is to assess the impact of changes to the methodology of calculating on values of the cost and employment effectiveness of basic forms of economic activation in Poland. They were introduced in 2015 in connection with ongoing discussion regarding the effectiveness of the evaluation methods used. The Ministry of Economic Development, Labour and Technology is currently responsible for activating the unemployed in Poland, and funds come from the Labour Fund. The analysis used is the regression discontinuity design. This analysis showed that significant changes occurred only in the slope of the regression line for cost effectiveness after 2015 for both procedures of its calculation. This shows that the new, introduced methods of calculating effectiveness were cosmetic in nature and did not significantly affect their values. A good recommendation for improving the method of evaluating forms of economic activation of the unemployed could be to extend the time of required employment.
Keywords: C21; J64; J68; 330; economic activation; effectiveness of activation; registered unemployment; regression discontinuity design